Seminar dan Pelatihan Arduino Berbasis Proyek Virtual Menggunakan Proteus sebagai Upaya Peningkatan Literasi Teknologi di SMK Negeri 1 Tanjung Tiram : Penelitian - Intan Zahar; Moraida Hasanah; Fynnisa Z; Derliana Hasibuan; Siti Ramadani; Dilla Atika Sury; Laura gusti Ayunda; Ali Usman; Sadun (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The development of digital technology in the Industrial Revolution 4.0 era requires vocational high school students to have strong technological literacy (Budiman & Ramdhani, 2022). However, limited hardware is a barrier, especially in the practice of Arduino microcontrollers (Lestari & Putra, 2020). This study aims to improve students' technological literacy through seminars and simulation training using Proteus software. A qualitative descriptive method was applied to 40 students majoring in Computer Engineering (TKJ) and Electronics at SMK Negeri 1 Tanjung Tiram. Activities included a basic Arduino seminar, simulation training on an Arduino Uno project using the HC-SR04 ultrasonic sensor, and evaluation through observation, tests, and questionnaires. The results showed that students were able to understand input-output, write simple code, and design virtual circuits (Santoso et al., 2023). They also experienced improvements in analysis, problem-solving, and learning motivation. The majority of participants considered the simulation easier to understand and encouraged interest in innovation (Karim & Yuliana, 2023). Thus, the use of Proteus effectively improves students' understanding and skills, while also being a solution to the limited practical facilities in vocational schools (Yusuf & Anwar, 2024).